Enhancing parents' confidence to care in acute childhood illness: triangulation of findings from a mixed methods study of Community Children's Nursing. (8th April 2013) - Callery, Peter; Kyle, Richard G.; Banks, Michele; Ewing, Carol; Kirk, Susan
Abstract Background Children's emergency hospital use is of concern internationally, but there has been little examination of home care by nurses. Aims To examine the care provided by community children's nurses during acute illness. Design Triangulation of findings from case studies of three Community Children's Nursing Teams. Methods Parents or carers (n = 763) completed questionnaires between 2008–2010 about their contacts with nurses and satisfaction with aspects and overall assessment of nursing care provided. Eighty‐one individuals participated in semi‐structured interviews: 29 parents/carers described their experiences and explained their questionnaire responses in more detail; 13 children talked about their care both in hospital and at home; and 39 nurses and other healthcare providers explained how nurses supported care of children at home. Questionnaire data were analysed descriptively and interview data qualitatively. The findings were integrated by triangulation of methods (questionnaires and interviews) and of data from different informants (children, parents, healthcare providers). Results Nursing care most frequently took the form of advice and education by either home visits or telephone contact. Parents and children were reassured by access to nurses and it gave them confidence to care at home. Most respondents thought that it reduced the time their children spent in hospital. Conclusions Nurses can make an important contribution to supporting parents to care confidently for their children at home to reduce or even to avoid hospitalization for acute conditions and give them confidence to manage future episodes of illness.